DNA barcoding of bats from two selected forest reserves in Peninsular Malaysia - SAIDATUL NUR HANIM ABDUL MALEK; IZZATI ADILAH AZMIR; NUR JULIANI SHAFIE; YUZINE ESA; WAN NURHAYATI WAN HANAFI (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Abdul Malek SNH, Azmir IA, Shafie NJ, Esa Y, Hanafi WNW. 2025. DNA barcoding of bats from two selected forest reserves in Peninsular Malaysia. Biodiversitas 26: 2843-2856. Bats (order Chiroptera) are notable for their species diversity and a variety of distinct characteristics. However, as several molecular studies have shown, morphological similarities in some taxa of this group can result in neglected diversity. DNA barcodes can help by providing an accurate, rapid, and effective method of species recognition. In this study, we used DNA barcoding to identify bats captured from two selected regions in Peninsular Malaysia: Kenyir, Terengganu and Taman Alam Liar Negeri Kenaboi (TALNK), Jelebu, Negeri Sembilan. DNA barcoding analysis was performed on 38 bat specimens to further verify the species identification of the captured bats from morphological characteristics. The COI gene (603-604 bp) was successfully sequenced from the 38 bat species, representing 3 families, 5 genera, and 15 species. The phylogenies of NJ, ML, and Bayesian methods resulted in most of the specimens of the same species being clustered together. According to the IUCN Red List, Rhinolophus trifoliatus is listed as Near Threatened (NT), whereas 14 species were listed as Least Concern (LC). The findings reported in this study confirm the usefulness of DNA barcoding to identify bat species and to measure bat diversity in Kenyir and TALNK forest reserves. Improving habitat conservation in forest reserves is necessary to guard against the disruption and extinction of bat species.